Rhomboid intramembrane protease YqgP licenses bacterial membrane protein quality control as adaptor of FtsH AAA protease - Began, Jakub; Cordier, Baptiste; Březinová, Jana; Delisle, Jordan; Hexnerová, Rozálie; Srb, Pavel; Rampírová, Petra; Kožíšek, Milan; Baudet, Mathieu; Couté, Yohann; Galinier, Anne; Veverka, Václav; et al. (The EMBO journal, 2020)
Magnesium homeostasis is essential for life and depends on magnesium transporters, whose activity and ion selectivity need to be tightly controlled. Rhomboid intramembrane proteases pervade the prokaryotic kingdom, but their functions are largely elusive. Using proteomics, we find that Bacillus subtilis rhomboid protease YqgP interacts with the membrane-bound ATP-dependent processive metalloprotease FtsH and cleaves MgtE, the major high-affinity magnesium transporter in B. subtilis. MgtE cleavage by YqgP is potentiated in conditions of low magnesium and high manganese or zinc, thereby protecting B. subtilis from Mn2+ /Zn2+ toxicity. The N-terminal cytosolic domain of YqgP binds Mn2+ and Zn2+ ions and facilitates MgtE cleavage. Independently of its intrinsic protease activity, YqgP acts as a substrate adaptor for FtsH, a function that is necessary for degradation of MgtE. YqgP thus unites protease and pseudoprotease function, hinting at the evolutionary origin of rhomboid pseudoproteases such as Derlins that are intimately involved in eukaryotic ER-associated degradation (ERAD). Conceptually, the YqgP-FtsH system we describe here is analogous to a primordial form of "ERAD" in bacteria and exemplifies an ancestral function of rhomboid-superfamily proteins.
Keywords: regulace genové exprese u bakterií; Gene Expression Regulation, Bacterial; Bacterial Proteins; ER-associated degradation; Membrane Proteins; membránové proteiny; endopeptidasy; Endopeptidases; ATPázy spojené s různými buněčnými aktivitami; intramembrane protease; Bacillus subtilis; proteostasis; membrane transporter; Proteomics; proteomika; bakteriální proteiny; ATPases Associated with Diverse Cellular Activities; rhomboid